AED-Associated Major Congenital Abnormalities - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The risk of major congenital abnormalities associated with maternal antiepileptic drug (AED) therapy during the first trimester of pregnancy was determined in 1,411 children born between 1972 and 1992 in four provinces in the Netherlands, and compared to 2000 nonepileptic matched controls.